PENGARUH GOOD CORPORATE GOVERNANCE, LIKUIDITAS, PERTUMBUHAN DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN YANG MENGIKUTI PROGRAM CORPORATE GOVERNANCE PERCEPTION INDEX PERIODE TAHUN 2012-2016 - Susana Dewi Astutik, 13.05.52.0234; Indarti, MG. Kentris (Students Journal of Accounting and Banking, 2017)
The purpose of this study is to examine the influence of Good Corporate Governance, Liquidity, Corporate Growth and Company Size on company performance following Corporate Governance Perception Index Program Period 2012-2016. The population is all companies that follow the Corporate Governance Program Perception Index Period 2012-2016. Sampling technique using purposive sampling. The sample criteria in this study are (a) Companies other than banking, insurance and financing. (b) The Company has complete data. (c) The financial statements are presented in Rupiah (d) Companies earning a positive net profit for the period of observation. Analyzer used is multiple linear regression. The results of the analysis can be concluded that: Good corporate governance has no significant effect on company performance (ROA). Liquidity has a positive and significant impact on company performance (ROA). Corporate growth has no significant effect on company performance (ROA). Company size has a positive and significant effect on company performance (ROA).Keywords: Good Corporate Governance, Liquidity, Corporate Growth, Company Size and Company Performance